2013
DOI: 10.1163/15685411-00002698
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional silencing of RNAi constructs against nematode genes in Arabidopsis

Abstract: In this research, Arabidopsis thaliana plants were transformed with hairpin constructs targeting cyst nematode (Heterodera schachtii) genes, driven by the cauUflower mosaic virus (CaMV) 35S promoter: two housekeeping genes (the splicing factor Hs-U2AF and the vacuolar Hs-W^ATPase) and one candidate effector gene (the ubiquitin extension protein Hs-ubi). Expression of the dsRNA appeared to be extremely variable between and within homozygous T3 lines and even between tissues. Infection experiments showed up to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…However, in planta delivery, such as that carried out here, is less effective than targeting the same genes by dsRNA soaking [ 37 , 38 ] and perhaps provides a more pragmatic assessment of this technology for control. The observed differences are likely a consequence of silencing efficiency using dsRNA delivered by the plant versus soaking nematode experiments [ 37 , 38 ], as other studies have indicated different levels of variability in silencing efficacy among transgenic events, expression levels of dsRNA, and lines bearing the same type of construct [ 52 ]. Furthermore, as root lesion nematodes are migratory nematodes, able to move in and out of the roots, the continuous exposure of nematodes to dsRNA delivered by the plant can be arrested or reduced for the periods of time that the nematodes will exit the roots, as a consequential effect of the dsRNA exposure, or ordinary movements of the nematodes, may allow for some degree of recovery.…”
Section: Resultsmentioning
confidence: 99%
“…However, in planta delivery, such as that carried out here, is less effective than targeting the same genes by dsRNA soaking [ 37 , 38 ] and perhaps provides a more pragmatic assessment of this technology for control. The observed differences are likely a consequence of silencing efficiency using dsRNA delivered by the plant versus soaking nematode experiments [ 37 , 38 ], as other studies have indicated different levels of variability in silencing efficacy among transgenic events, expression levels of dsRNA, and lines bearing the same type of construct [ 52 ]. Furthermore, as root lesion nematodes are migratory nematodes, able to move in and out of the roots, the continuous exposure of nematodes to dsRNA delivered by the plant can be arrested or reduced for the periods of time that the nematodes will exit the roots, as a consequential effect of the dsRNA exposure, or ordinary movements of the nematodes, may allow for some degree of recovery.…”
Section: Resultsmentioning
confidence: 99%
“…Pre-immune (g); anti-30D08 antibody (h). New Phytologist is useful for confirming dsRNA expression in select lines for analysis; however, it does not always correlate with RNA silencing efficiency of the target gene (Patel et al, 2008;Kyndt et al, 2013). Transgenic 30D08 RNAi lines exhibited similar morphological features to that of wild-type, plants confirming no offtarget effects in the growth and development of transgenic plants.…”
Section: Matylfiaaaafgagiycwkaylgpmldqpksddeek------------------kag Hmentioning
confidence: 99%
“…Position effects frequently are reported in potato and can override the regulatory control of the pro moter associated with the transgene, such that the tran script level, as well as the temporal and spatial expression patterns of the transgene are altered (Meiyalaghan et al, 2006;Barrell & Conner, 2009;Jacobs et al, 2009;Bar rell et a l, 2013). It has been shown that in A. thaliana methylation of the 35S promoter can cause epigenetic si lencing of transgenic RNAi constructs, leading to strongly varying levels of small RNAs between lines (Kyndt et al, 2013). Thus, it is possible that in some cases one or more 16D10i-2 RNAi transgene copies were partially or fully deactivated in similar ways, thereby resulting in double or multiple insertion lines that produce small RNAs at a level equivalent to what would be expected in single insertion lines.…”
Section: Meloidogyne Chitwoodi Rnai Resistance In Potatomentioning
confidence: 99%